ChemInform Abstract: A General and Efficient Palladium‐Catalyzed Carbonylative Synthesis of 2‐Aryloxazolines and 2‐Aryloxazines from Aryl Bromides. Issue 12 (14th March 2013) - Wu, Xiao‐Feng; Neumann, Helfried; Neumann, Stephan; Beller, Matthias
Abstract A wide range of aromatic and heteroaromatic bromides is applied.